The Aid Chain: Coercion and Commitment in Development NGOs - Wallace, Tina; Bornstein, Lisa; Chapman, Jennifer (Practical Action, 2007)
Significant proportions of aid already flow through the non-government al sector, but questions are increasingly being asked about the role o f NGOs and whether they can deliver on their ambitious claims. This st udy examines conditionality and mutual commitment between internationa l aid donors and recipient NGOs, North and South. Fieldwork and case s tudy material from Uganda and South Africa are used to support the aut hors’ contention that the fast changing aid sector has–in the context of a dynamic policy environment–encouraged the mainstreaming of a mana gerial approach that does not admit of any analysis of power relations or cultural diversity. This increasing–essentially technical– definit ion of the roles of NGOs has worked to limit the extent of the very de velopment that the organizations were initially established to promote .